Disease X: Unraveling a mysterious outbreak in the Democratic Republic of the Congo - Verma, Manali; Verma, Amogh; Singla, Rahul; Sharma, Siddharth; Suresh, Vinay; Karim, Hajira; Tafawa, Chelsea Rachael (My University, 2025)
...
Keywords: Democratic Republic of the Congo; Disease X; Emerging Infectious Diseases; Global Health; Public Health